The integration of blended learning into the undergraduates occupational therapy curriculum - Barnard-Ashton, Paula Monique (My University, 2018)
The Department of Occupational Therapy (DOT) recognised the threat of massification to the ability to graduate professional and competent generalist occupational therapists. Successrates were dropping in the diversified student body and lecturer workload was increasing, contributing to poor research publication output. Blended Learning (BL) was suggested as a strategic opportunity to manage the undergraduate occupational therapy curriculum which was delivered through Problem Based Learning (PBL). The researcher was nominated to take the lead in driving the process, initiating this Participatory Action Research (PAR). Over six academic years the lecturers of the DOT, through Legitimate Peripheral Participation (LPP), participated in curriculum redesign and content development activities, which crafted the BL process. The PAR research design facilitated the insider positionality of the researcher to investigate the impact of BL on teaching and learning within the DOT. The stakeholders in the study were the lecturers of the DOT, the students enrolled in the Bachelor of Sciences in Occupational Therapy degree between 2010 and 2015, and the School e-Learning Project team. Quantitative and qualitative methodologies were employed throughout the PAR. Quantitative data were analysed for effect due to the small student and staff population. Qualitative data were analysed using Strauss’ grounded theory and Brookfield’s lenses of critical reflection. This thesis presents five papers of which two are macro-level PAR studies and three are micro-level PAR studies. The results yielded two core themes: the drivers of change and the outcomes of BL. The outcomes of BL demonstrated that when integrating BL over a long-term intervention the effect of habituation on student performance is positive, students perceive BL to have a positive effect on their knowledge gain and that when BL activities have the ‘just right challenge’ students are interested in the learning process and find it beneficial to their learning. The six drivers of change provide guideline criteria to consider when integrating BL into PBL curricula with similar contexts; namely: Buy-in and goodness of fit, Being evidence-based, Just do it!, Support, Students are primed for BL, and the hurdles to BL. The lecturers of the DOT believe that ‘there is no going back!” Ethical clearance for this thesis was issued through the Human Research Ethics Committee (Medical) with the following numbers: M090920, M160877 and M141168 (refer Appendix A) The originality report through Turnitin presented in Appendix B shows 14% similarity when the two published articles are excluded.
Original published work submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2018